TRAFFIC AND ROAD STUDY IN CONSTANTINE CITY: ANALYSIS OF TRAFFIC IN CONSTANTINE CITY - Cherouana Rabiaa,; Chaouche Teyara Roubila, (International Journal of Innovative Technologies in Social Science, 2024)
This study primarily aims to shed light on the traffic and road conditions in the city of Constantine. As a crucial measure in the transportation sector, traffic and road studies play a pivotal role in evaluating the efficiency of existing road networks, determining current and future traffic volumes, identifying bottlenecks, and proposing solutions through traffic redistribution and planning. To assess the current state of traffic and roads in Constantine and their adequacy in relation to the city's area and population, this study was conducted. Constantine was chosen due to its unique position as a hub for numerous major roads with high traffic volumes. Six out of the seven national roads traversing the entire province pass through Constantine. To comprehensively address the subject, the research is divided into three main sections:- Section One: Provides essential definitions related to the topic, such as road network, road capacity, traffic volume, etc. - Section Two: Delves into the details of traffic volume, its types, methods, and the significance of its study. - Section Three: Conducts a detailed analysis of traffic volume and roads in Constantine. Initially, the study relies on the administrative classification of roads to identify those within the study area. Subsequently, it analyzes the average traffic volume and traffic density on these roads.